2020
DOI: 10.3389/fmars.2020.587686
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Structure and Gene Expression Plasticity of the Deep-Sea Vent and Seep Squat Lobster Shinkaia crosnieri

Abstract: Population Connectivity and Deep-Sea Adaptation structure of S. crosnieri using transcriptome-wide SNP markers resulted in an improved understanding of its molecular adaptation and expression plasticity in vent and seep ecosystems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 88 publications
(100 reference statements)
2
16
0
Order By: Relevance
“…Under such a condition, these limpets are also exposed to methane along with other toxic substances from their ambient environment and thus need to evolve suitable strategies for detoxification. Considering that the metabolism of xenobiotics by cytochrome P450 (ko00980) and glutathione metabolism (ko00480) pathways were significantly enriched from the top 10% most abundant transcripts, we investigated the expression of the mixed-function oxygenase (MFO) system components cytochrome P450 (CYP), conjugating enzyme glutathione S-transferase (GST), antioxidant enzymes superoxide dismutase (SOD), and glutathione peroxidase (GPX) ( Lee, 1981 ; Ramos and Garcia, 2007 ; Xiao et al., 2020 ). Seven transcripts of CYP, twelve transcripts of GST, three transcripts of SOD, and one transcript of GPX ranked in the top 10% ( Figure 6 and Table S6 ), indicating high MFO system and antioxidant enzyme activities in the limpet B. lactea , which might be responsible for the xenobiotic detoxification.…”
Section: Resultsmentioning
confidence: 99%
“…Under such a condition, these limpets are also exposed to methane along with other toxic substances from their ambient environment and thus need to evolve suitable strategies for detoxification. Considering that the metabolism of xenobiotics by cytochrome P450 (ko00980) and glutathione metabolism (ko00480) pathways were significantly enriched from the top 10% most abundant transcripts, we investigated the expression of the mixed-function oxygenase (MFO) system components cytochrome P450 (CYP), conjugating enzyme glutathione S-transferase (GST), antioxidant enzymes superoxide dismutase (SOD), and glutathione peroxidase (GPX) ( Lee, 1981 ; Ramos and Garcia, 2007 ; Xiao et al., 2020 ). Seven transcripts of CYP, twelve transcripts of GST, three transcripts of SOD, and one transcript of GPX ranked in the top 10% ( Figure 6 and Table S6 ), indicating high MFO system and antioxidant enzyme activities in the limpet B. lactea , which might be responsible for the xenobiotic detoxification.…”
Section: Resultsmentioning
confidence: 99%
“…To date, only four studies have examined genetics across at least two Indian ridges and reported population connectivity of six different species (Chen et al, 2015;Watanabe et al, 2018;Sun et al, 2020;Zhou et al, 2022). However, recent work on population plasticity and genetic structure of the deep-sea mussel Bathymodiolus platifrons (Xu et al, 2017), the deep-sea limpet Bathyacmaea nipponica (Xu et al, 2021), and the deep-sea squat lobster Shinkaia crosnieri (Xiao et al, 2020) clearly showed that populations of these species from vent and cold-seep fields thousands of kilometers apart in the west Pacific Ocean could be well connected. Hydrodynamics plays a more important role than habitats or geographic distance in driving the gene flow and divergence for these populations (Xiao et al, 2020;Xu et al, 2021).…”
Section: The Ecology Of Indian Ocean Vent Fieldsmentioning
confidence: 99%
“…However, recent work on population plasticity and genetic structure of the deep-sea mussel Bathymodiolus platifrons (Xu et al, 2017), the deep-sea limpet Bathyacmaea nipponica (Xu et al, 2021), and the deep-sea squat lobster Shinkaia crosnieri (Xiao et al, 2020) clearly showed that populations of these species from vent and cold-seep fields thousands of kilometers apart in the west Pacific Ocean could be well connected. Hydrodynamics plays a more important role than habitats or geographic distance in driving the gene flow and divergence for these populations (Xiao et al, 2020;Xu et al, 2021). These findings (and unpublished data on population genetics and connectivity from Qian Pei-Yuan's laboratory) clearly demonstrate that population genomic surveys should be applied to future population connectivity studies of deepsea animals.…”
Section: The Ecology Of Indian Ocean Vent Fieldsmentioning
confidence: 99%
“…A major impediment to collating the body of data and evidence necessary to generalize about how the hadal trenches shape patterns of intraspecific genetic structure is the sheer logistical challenge of sampling the deep sea at an appropriate geographical scale and for an adequate number of individuals (Jamieson et al, 2010). Indeed, many of the high‐profile studies on deep‐sea genetic structure work within a phylogeographical rather than a population genetic framework (Baco et al, 2016; Havermans et al, 2013; Taylor & Roterman, 2017), focus on topographic features such as hydrothermal vents with a proclivity for marked genetic structure driven by natural selection (Vrijenhoek, 2010; Xiao et al, 2020), or confirm hypotheses of wide‐ranging dispersal in cosmopolitan species from relatively sparse sampling (France & Kocher, 1996). Advances in autonomous underwater vehicle technology have increased the capability for sampling the deep sea in a more systematic and less opportunistic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many of the high-profile studies on deep-sea genetic structure work within a phylogeographical rather than a population genetic framework (Baco et al, 2016;Havermans et al, 2013;Taylor & Roterman, 2017), focus on topographic features such as hydrothermal vents with a proclivity for marked genetic structure driven by natural selection (Vrijenhoek, 2010;Xiao et al, 2020), or confirm hypotheses of wide-ranging dispersal in cosmopolitan species from relatively sparse sampling (France & Kocher, 1996). Advances in autonomous underwater vehicle technology have increased the capability for sampling the deep sea in a more systematic and less opportunistic manner.…”
Section: Introductionmentioning
confidence: 99%